Improving systemic therapy selection for inflammatory skin diseases: A clinical need surveyCapsule Summary - Nicholas D. Brownstone, MD; Aaron S. Farberg, MD; Graham H. Litchman, DO, MS; Ann P. Quick, PhD; Jennifer J. Siegel, PhD; Lenka V. Hurton, PhD; Matthew S. Goldberg, MD; Peter A. Lio, MD (Elsevier, 2024)
Background: Empirical decisions to select therapies for psoriasis (PSO) and atopic dermatitis (AD) can lead to delays in disease control and increased health care costs. However, routine molecular testing for AD and PSO are lacking. Objective: To examine (1) how clinicians choose systemic therapies for patients with PSO and AD without molecular testing and (2) to determine how often the current approach leads to patients switching medications. Methods: A 20-question survey designed to assess clinician strategies for systemic treatment of AD and PSO was made available to attendees of a national dermatology conference in 2022. Results: Clinicians participating in the survey (265/414, 64% response rate) ranked "reported efficacy" as the most important factor governing treatment choice (P < .001). However, 62% (165/265) of clinicians estimated that 2 or more systemic medications were typically required to achieve efficacy. Over 90% (239/265) of respondents would or would likely find a molecular test to guide therapeutic selection useful. Limitations: To facilitate ease of recall, questions focused on systemic therapies as a whole and not individual therapies. Conclusion: Clinicians want a molecular test to help determine the most efficacious drug for individual patients.